There is No Hop(p)e neboli Blaise Pascal a ambivalence kosmické hrůzy - Zika, Richard; Váša, Ondřej (Filosoﬁcký časopis)
The essay focuses on the survival of Pascal’s metaphors concerning the cosmic wasteland. It analyzes step-by-step the ways in which authors such as Immanuel Kant, George Milbrey Gould, Herbert George Wells, Thomas Henry Huxley, Howard Phillips Lovecraft, Vladimír Hoppe, Jacques Monod, and Eugene Thacker appropriated Pascal’s images of despair from the “eternal silence of infinite spaces”, which they have then used to develop their own arguments in favor of defending (or disparaging) the relevance of a human presence in the universe. The focus of the study lies in an analysis of these connections in the work of the Czech philosopher Vladimír Hoppe.